Institutional Agenda and PPP Options for Water Supply and Sewage in Ludhiana - Ramanujam, S.R. (World Bank, Washington, DC, 2015)
Water supply and sewage (WSS) operations in Ludhiana resemble that of many Indian cities; service levels are poor when compared to benchmarks; cost recovery is low; the municipal corporation subsidises operating deficits; the Government finances capital expenditure; assets are created through a State owned entity; internal capacity, systems and procedures are weak. The State Government has taken a decision to make key municipal corporations (including Ludhiana) responsible for future asset creation and also expects them to share capital expenditure. To improve the quality of service, the city needs immediate capital investments and change in management practices. Key institutional actions to achieve this are a) WSS operations focusing on higher cost recovery, b) increased contribution from the municipal corporation to WSS capital expenditure financing as opposed to O & M financing and c) modern governance structure for WSS operations.